2014
DOI: 10.1088/1367-2630/16/3/039501
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum: Nuclear magnetic resonance characterization of the stationary dynamics of partially saturated media during steady-state infiltration flow (2011 New J. Phys. 13 015007)

Abstract: Due to the incorrect use of the inlet tubing diameter, 1.9 mm, rather than the bead pack diameter, 10 mm, to determine the velocity of the wetting fluid v w , the capillary numbers Ca calculated were incorrect by a factor 27.70.The horizontal axes for Ca in figure 3(b) and figure 5 should be divided by a factor of 27.70, and hence range from 3.61e-6 to 7.22e-5. This does not impact any of the discussion or the conclusions drawn in the original publication. A corrected version of figure 5 is reproduced below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…(1) using a very similar model with only BP, also reports similar dependency of β on saturation with a visible curvature in the scaling plots. These clearly indicate a non-zero ∆P c that has been ignored hence resulting in a wandering value of β. Interestingly, the same experimental data by Rassi et al [15] are found consistent with β = 1/2 when reanalyzed using Eq. (3) [22].…”
supporting
confidence: 75%
See 2 more Smart Citations
“…(1) using a very similar model with only BP, also reports similar dependency of β on saturation with a visible curvature in the scaling plots. These clearly indicate a non-zero ∆P c that has been ignored hence resulting in a wandering value of β. Interestingly, the same experimental data by Rassi et al [15] are found consistent with β = 1/2 when reanalyzed using Eq. (3) [22].…”
supporting
confidence: 75%
“…where β = 0.54 ± 0.08. More recently, Rassi et al [15] have measured the exponent β which varies in the range of 0.3 to 0.45 depending on the saturation, in steady-state two-phase flow of water and air in a three-dimensional porous medium constructed from glass beads.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The exponent a has been found to be in a range of 0.3 to 0.6, both from theoretical arguments as experimental measurements on small samples and simplified systems (e.g. micromodels and bead packs) (Rassi et al, 2014;Sinha et al, 2017;Tallakstad et al, 2009). Figure 12 shows the measured pressure gradients ∇P as a function of Ca for our experiments.…”
Section: Representative Elementary Volumementioning
confidence: 72%
“…This represents a reduction in the resistance to flow compared to Darcy's law, as the fluid distributions (intermittently) change in a way that reduces viscous dissipation. The exponent a has been found to be in a range of 0.3–0.6, both from theoretical arguments as experimental measurements on small samples and simplified systems (e.g., micromodels and bead packs) (Rassi et al., 2014; Sinha et al., 2017; Tallakstad et al., 2009). Figure 12 presents the relationship of measured pressure gradients ∇ P and Ca for our experiments.…”
Section: Resultsmentioning
confidence: 99%